2023
DOI: 10.1177/21676968231170247
|View full text |Cite
|
Sign up to set email alerts
|

Social Withdrawal, Solitude, and Existential Concerns in Emerging Adulthood

Abstract: This study aimed to investigate the ways subtypes of social withdrawal and dimensions of solitude are related to existential concerns in emerging adulthood. The links between social withdrawal/solitude and existential well-being are a highly neglected research issue. Participants were 774 emerging adults (50.4% males) aged 18–25 ( M = 20.07) from Greece. They completed measures on social withdrawal, solitude, authenticity, meaning in life, existential anxiety, and existential loneliness. We used structural equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…It is also robustly related to internalizing problems (e.g., negative affect, social anxiety, loneliness) and peer difficulties (e.g., rejection, victimization) from early childhood through emerging adulthood [31,33]. Among emerging adults, shyness has demonstrated associations with depressive symptoms, existential concerns, test anxiety, and lower levels of academic self-efficacy [16,34]. Indeed, Closson et al [35] found that shy young adults reported the lowest levels of social support, happiness, life satisfaction, and self-worth compared to other groups of withdrawn and non-withdrawn peers.…”
Section: Implications Of Motivations For Social Withdrawal In Emergin...mentioning
confidence: 99%
“…It is also robustly related to internalizing problems (e.g., negative affect, social anxiety, loneliness) and peer difficulties (e.g., rejection, victimization) from early childhood through emerging adulthood [31,33]. Among emerging adults, shyness has demonstrated associations with depressive symptoms, existential concerns, test anxiety, and lower levels of academic self-efficacy [16,34]. Indeed, Closson et al [35] found that shy young adults reported the lowest levels of social support, happiness, life satisfaction, and self-worth compared to other groups of withdrawn and non-withdrawn peers.…”
Section: Implications Of Motivations For Social Withdrawal In Emergin...mentioning
confidence: 99%